The Role of Mental Health Literacy and Resilience in Fostering Mental Well-Being among High School Students - Wijaya, Daniswara Agusta; Widyorini, Endang; Utami, Margaretha Sih Setija (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Recently, studies related to mental health have switched focus toward mental well-being promotion among all age groups, including students in high school level. Taking into account several factors that influence mental well-being, this study investigated mental health literacy (MHL), mental health promoting knowledge (MHPK), and resilience. This research aims to examine the predicting effect of MHL and MHPK on mental well-being, mediated by resilience. A total of 792 participants, who were recruited conveniently from a private school in Semarang, Indonesia, completed several instruments named MHLQ-SV, MHPKS, BRS, and WEMWBS. Results presented that both MHPK and MHL predict the level of high school students’ mental well-being mediated by resilience. Furthermore, MHPK was observed to contribute more to mental well-being compared to MHL. Hence, mental health intervention programs should incorporate a positive psychology approach to ensure the effectivity of the programs on resilience, leading to mental well-being enhancement.